Study on Water Injection Indicator Curve Model in Fractured Vuggy Carbonate Reservoir. (21st August 2021) - Yong, Wang; Hanqiao, Jiang; Junjian, Li
Abstract : Fractures and cavities are very well developed in fractured vuggy carbonate reservoirs in Tahe Oilfield, showing obvious constant volume or approximate constant volume characteristics, and the development of karst vuggy reservoirs is characterized by strong randomness, locality, heterogeneity, and discontinuous development, which has a great impact on oilfield development effect. The application of conventional reservoir engineering methods in this kind of reservoir has many limitations. The traditional water injection indication curve is mainly based on a sandstone reservoir, ignoring the elastic energy of the water body in a reservoir and the combination relationship of fracture and cavity, which can not meet the needs of the carbonate reservoir. According to the principle of volume balance of constant volume body and considering the elastic energy of original formation water, a new model of improved water injection indication curve and the original water-oil ratio of carbonate reservoir is proposed, and the chart of water injection indication curve is established. Compared with other methods, this method has the advantages of low cost and accurate identification results. The calculated reservoir parameters such as single well-controlled reserves, well-controlled water volume, and original water-oil ratio have high reliability, and the chart is easy to use. The model is applied to the Yuejin block of Tahe Oilfield, and the results show that the improved model is consistent with the results of other test methods, such as high-precision seismic combined with fracture cavity carving technology, which indicates that the model has strong reliability.